A Direct Path to Dependable Software. - Jackson, Daniel (Communications of the ACM, 2009)
The article discusses efforts to make computer software more dependable, examining requirements for computer software developers to produce direct evidence that their software is dependable. Advantages to this approach include greater credibility and reduced costs, the author suggests. Topics include the lack of databases in the software industry that record the causes or effects of software failure and industry data that would support software developers efforts to improve design and development strategies.